Enhancing Arabic Vocabulary Mastery in Primary Students through Powtoon-Based Web Media - Rahmah, Hasifatur; Fauji, Imam (Indonesian Journal of Islamic Studies, 2024)
This study investigates the impact of utilizing Powtoon-based web media on the mastery of Arabic vocabulary (mufrodaat) among fourth-grade students at SD Muhammadiyah 09 Ngaban. Twenty students participated as research subjects, and quantitative data analysis techniques were employed. Data collection involved pretests, posttests, observations, and documentation. The study revealed a noteworthy average N-Gain score of 0.515, indicating a moderate effect of Powtoon media on students' Arabic vocabulary mastery. These findings underscore the potential of web-based media in augmenting language acquisition and offer practical insights for educators aiming to optimize vocabulary instruction. Highlight: This study assesses the impact of Powtoon-based web media on Arabic vocabulary acquisition in fourth-grade students. Quantitative data analysis and various assessment methods were employed to measure the effectiveness of the intervention. The research highlights the potential of web-based media in enhancing language learning outcomes, providing valuable insights for educators in vocabulary instruction optimization. Keyword: Arabic Vocabulary Mastery, Powtoon-Based Web Media, Language Acquisition, Educational Impact, Vocabulary Instruction Enhancement